Clinically Relevant Enterococcus Species and PCR Screening of Antibiotic Resistance and Virulence Factor Coding Genes: Life Sciences-Microbiology - Varghese, Jijo G; B, Anandharaj; E, Fiji (International Journal of Life Science and Pharma Research, 2022)
Enterococci are Gram positive cocci which are common residence of gastro intestinal tracts of humans and animals. But they are capable of causing severe infections, most often in hospitalised patients. Enterococci are important nosocomial pathogens and their intrinsic property of antibiotic resistance makes treatment difficult. Against this clinical significance, a study was conducted on the prevalence of vancomycin resistant enterococcal infections and their antibiotic sensitivity patterns at Sunrise Institute of Medical Sciences, a tertiary care hospital in Kochi, Kerala state. Various clinical specimens like blood, urine, abscess, vaginal swab etc. were microbiologically screened for the presence of antibiotic resistant Enterococci. The common phenotyping methods and genotyping protocols were used to identify the species for the study. The vancomycin resistant strains were typed genotypically by using 16S rDNA sequencing and the isolates were speciated to be E. faecium. A molecular screening of the isolates was also done for the presence of various virulence factor coding genes and for the genes which confer antibiotic resistance. The findings of the study revealed that 89.1 % isolated strains were multidrug resistant and a total of 4 antibiotic resistance genes were detected. Among the isolates the vancomycin resistance genes vanA, vanB; tetracycline resistance genes tetA and macrolide resistance gene ermA were screened. The presence of genes coding for various virulence factors were also detected among the isolates. However, we present an overview of antibiotic resistance pattern and virulence factors present in enterococci and we strongly believe that these results will surely help to design a new disinfection regime and antibiotic stewardship to control the incidence of infection.